The JWST/PASSAGE Survey: Testing Reionization Histories with JWST’s First Unbiased Survey for Lyα Emitters at Redshifts 7.5–9.5 - Axel Runnholm; Matthew J. Hayes; Vihang Mehta; Matthew A. Malkan; Claudia Scarlata; Kalina V. Nedkova; Marc Rafelski; Benedetta Vulcani; Mason Huberty; E. Christian Herenz; Anne Hutter; Sean Bruton; et al. (The Astrophysical Journal)
Ly α emission is one of a few observable features of galaxies that can trace the neutral hydrogen content in the Universe during the Epoch of Reionization (EoR). To accomplish this, we need an efficient way to survey for Ly α emitters (LAEs) at redshifts beyond 7, requiring unbiased emission-line observations that are both sufficiently deep and wide to cover enough volume to detect them. Here we present results from PASSAGE—a pure-parallel JWST/NIRISS slitless spectroscopic survey to detect LAEs deep into the EoR, without the bias of photometric preselection. We identify four LAEs at 7.5 ≤ z ≤ 9.5 in four surveyed pointings and estimate the luminosity function (LF). We find that the LF does show a marked decrease compared to post-reionization measurements, but the change is a factor of ≲10, which is less than expected from theoretical calculations and simulations, as well as observational expectations from the pre-JWST literature. Modeling of the intergalactic medium and expected Ly α profiles implies that these galaxies reside in ionized bubbles of ⪆2 physical Mpc. We also report that in the four fields we detect {3, 1, 0, 0} LAEs, which could indicate strong field-to-field variation in the LAE distribution, consistent with a patchy H i distribution at z  ∼ 8. We compare the recovered LAE number counts with expectations from simulations and discuss the potential implications for reionization and its morphology.